Estudos do tratamento de águas residuárias do café usando coagulação e processos de oxidação avançada - Colpa, Poliana Coste e (2023)
"STUDIES ON COFFEE WASTEWATER TREATMENT USING COAGULATION AND ADVANCED OXIDATION PROCESSES" Brazil leads global coffee production, accounting for more than one-third of the global production and playing a crucial role in the national economy. Post-harvest coffee bean management includes the wet processing method. The residues generated in this process are known as coffee wastewater (CWW). Therefore, it is necessary to study an alternative treatment for the CWW generated in the wet processing of coffee produced at IFSULDEMINAS, Campus Muzambinho. This work proposes the treatment of CWW using coagulation and Advanced Oxidation Processes (AOPs) as treatment methods. Initially, it was necessary to analyze some parameters of the CWW samples, such as: total solids mass concentrations, total suspended solids, total volatile solids, turbidity, pH, conductivity, Chemical Oxygen Demand (COD), and Total Organic Carbon (TOC). Due to high turbidity values (279.0 NTU) and COD (9067.0 mg L-1), it was adopted to always perform a coagulation pre-treatment using aluminum sulfate. This process removed about 97% of turbidity and 20% of COD from the CWW samples. For the electro-Fered-Fenton process, an electrochemical system was used (with a titanium anode coated with ruthenium dioxide and titanium dioxide (DSA – Dimensionally stable anode), and two AISI 304 stainless steel cathodes). In this treatment, it was possible to achieve a COD removal of approximately 78% and 95% turbidity removal. For the photo-electro-Fered-Fenton process, there was an efficiency of COD removal of around 86% and 95% turbidity removal. For comparison of treatment efficiency, the Fered-Fenton processes were used, obtaining a COD removal of about 83% and 95% turbidity removal, and photo-Fered-Fenton, where the COD and turbidity removal were 87% and 97%, respectively. These results indicate a better removal efficiency using the photo-Fered-Fenton treatment, which also shows a 70% TOC removal. Despite the slightly lower efficiency of the photo-electro-Fered-Fenton treatment, the photo-Fered-Fenton has a lower cost since it does not use electrical current and does not require an electrochemical system and electrodes, making the process simpler. With this treatment, the removal percentage recommended by current legislation is achieved, considering a minimum COD removal of 80%.